Application of Citrus By-Products in the Production of Active Food Packaging - Lourdes Casas Cardoso; Cristina Cejudo Bastante; Casimiro Mantell Serrano; Enrique J. Martínez de la Ossa (MDPI AG, 2022)
Some citrus by-products such as orange peel contains valuable compounds that could be recovered and restored into the food chain. In this study, an efficient valorization of orange peel has been investigated using green extraction, fractionation, and impregnation techniques. The first step included its extraction using CO2 and ethanol under different pressure (200-400 bar) and temperature (35-55 °C) conditions. The extracts obtained at 300 bar and 45 °C showed strong antioxidant with moderate antimicrobial activity. Then, the extract was subjected to a sequential fractionation process. The fraction obtained at 300 bar, 45 °C, and using 32% ethanol showed the strongest antioxidant and antimicrobial activity with a high extraction yield. Finally, the potential of the two best extracts (obtained at 400 bar and 45 °C before any fractionation and the fractions obtained at 300 bar, 45 °C using 32% ethanol) was determined by conducting an impregnation process to obtain an antioxidant food-grade rigid plastic that would preserve fresh food. The percentage of cosolvent (1 and 2% ethanol), the impregnation time (1 and 3 h), the pressure (200 and 400 bar), and the temperature (35 and 55 °C) were evaluated as variables of this process. The impregnated plastic showed good antioxidant and antimicrobial activities.